АДМИНИСТРАТИВНОЕ РЕГУЛИРОВАНИЕ СОЦИАЛЬНОЙ СФЕРЫ И ПРОФИЛАКТИКА НАРКОМАНИИ СРЕДИ МОЛОДЁЖИ В РЕСПУБЛИКЕ УЗБЕКИСТАНА - Ж.А.Мажидов; Исломов Исохон Исмаилович (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the system of administrative regulation of the social sphere in the Republic of Uzbekistan in the context of combating drug abuse among youth. The normative and legal framework is analyzed, including the Constitution of the Republic of Uzbekistan, the Law of the Republic of Uzbekistan “On Narcotic Drugs,” the Code of Administrative Responsibility, the Law “On Narcotic Drugs and Psychotropic Substances,” and the National Strategy for 2024–2028. The study explores administrative measures, preventive raids (“Qora mak,” “Qora zaxri”), preventive programs implemented in educational institutions, the activities of the « Mahalla Yettiligi» system, and digital monitoring mechanisms. Current statistics on drug-related crime and youth involvement are presented. Special attention is paid to the need to maintain a balance between law enforcement measures and educational and preventive approaches. The article formulates proposals for further improvement of administrative regulation, taking into account contemporary challenges associated with the spread of synthetic drugs.